Environmental impact of car wash services by performing life cycle perspective - I. Firmansyah; A.D. Santoso; N. Nuha; F.L. Sahwan; F. Suryanto; S. Wahyono (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The car wash industry has grown rapidly globally, spurred by increasing vehicle ownership and demand for convenient services. However, this sector is linked to environmental challenges, including excessive water consumption, chemical runoff, and high energy use. This is the first life cycle assessment to assess the environmental impact of vehicle wash services in Indonesia, focusing on water usage, chemical discharge, energy consumption, and waste creation in car wash operations.METHODS: The life cycle assessment method was employed to assess three stages of car wash processes including wet processing, dry processing, and chemical usage from water supply to waste management. The functional unit, defined as the washing of a single vehicle, serves as the reference point for data inventory and impact assessments. A sensitivity study was performed to evaluate the robustness of the results by analysing the impact of fluctuating electricity consumption.FINDINGS: The result showed that automated car wash systems consume between 150-190 liters of water per wash, while manual services use approximately 100-120 liters. Chemical runoff, including detergents, surfactants, and heavy metals, poses a significant threat to aquatic ecosystems, especially in areas with inadequate wastewater treatment infrastructure. Energy consumption, driven by the use of high pressure pumps and dryers, contributes substantially to greenhouse gas emissions and fossil fuel depletion. Sensitivity analysis indicates that energy consumption is a key driver of environmental impact, particularly in regions relying on coal-based power grids. The study further explores mitigation strategies such as water recycling systems, the adoption of biodegradable detergents, and the integration of renewable energy sources into car wash operations. These practices are shown to reduce water usage by up to 60 percent decrease chemical runoff, and cut energy related emissions by approximately 30 percent.CONCLUSION: The findings underscore the need for regulatory reforms and industry wide adoption of sustainable practices to minimize the environmental footprint of car wash services. This study contributes new insights into the sustainability of this growing industry and offers actionable recommendations for reducing its ecological impact.